PEMANFAATAN TEKNOLOGI INFORMASI PADA SEKOLAH MENENGAH ATAS DI BELINYU (Jurnal AbdiMas Nusa Mandiri, 2024)
The implementation of infrastructure and development of information technology (IT) services in educational environments such as schools and campuses plays an important role in supporting quality learning experiences. Regarding the introduction of IT infrastructure and service development in the educational environment. IT infrastructure covers various aspects such as providing hardware and software to meet educational needs, providing a reliable communications network, and ensuring data and information security. Services provided include training for teachers in the use of learning technology, technical support for students and staff, as well as implementation of related policies. With the right infrastructure, students and lecturers can access learning resources efficiently and interact in a technology-integrated learning environment. This service also plays an important role in increasing the technological literacy of students and teachers and ensuring the smooth operation of systems in educational environments. The services provided at schools can have a positive impact on improving the quality of education, preparing students to face the challenges of the digital world, and creating an inclusive and innovative learning environment. A holistic and coordinated implementation approach and ongoing support from all stakeholders will be key to achieving this goal.
Keywords: information technology; infrastructure; schools; students; teachers